Influence of the political party governing a territory in the progress of measures related to the Sustainable Development Goals. Comparative study in Spain - Gil Ibáñez, Marta; Solans Oncala, Núria (REVESCO. Revista de Estudios Cooperativos, 2025)
Public policies are essential in advancing the implementation of laws that favour the fulfilment of the tenth Sustainable Development Goal (SDG): the reduction of inequalities. In Spain there have been changes in the social and economic inequalities of its inhabitants, although the evolution has not been the same in all territories. This study relates the evolution of indicators of gender equality, quality of education, people with disabilities and immigrants, and poverty according to the territory and its rulers. Specifically, it seeks to determine whether or not there is a relationship between the differentiated evolution between territories and the political party in power. To this end, a statistical clustering method has been implemented. As a main conclusion, no relationship between both variables has been detected, registering similar evolutions in territories governed by political parties of different ideology.